2013
DOI: 10.4018/ij3dim.2013070101
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Reality: Revealing the BIM Gap Between the UK and Turkey

Abstract: The complex nature of the construction process needs an intensive control and management mechanism in order to manage and process information flow. Current deficiencies in managing construction related information have been highlighted by a range of industry reports, the consensus of which has reinforced the lack of performance in the construction industry. Given this, recent research on the role of Building Information Modelling (BIM) has been proffered as a potential solution for covering these deficiencies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The application of BIM technology in PBPs is a good example. BIM is committed to addressing the omission and asymmetry of information across the interface through a standardized information model [78,92,93], which can ensure the integrity and accuracy of information. In addition, the timeliness of information communication is also identified as a challenge of interface management [57,72,73].…”
Section: Information Communication (Cluster 1)mentioning
confidence: 99%
“…The application of BIM technology in PBPs is a good example. BIM is committed to addressing the omission and asymmetry of information across the interface through a standardized information model [78,92,93], which can ensure the integrity and accuracy of information. In addition, the timeliness of information communication is also identified as a challenge of interface management [57,72,73].…”
Section: Information Communication (Cluster 1)mentioning
confidence: 99%
“…The technical environment was confirmed to significantly affect interface management (H3a, 0.177). The use of BIM and other technologies breaks the boundaries of participants in time and space and provides a unified platform for interface management [54]. Technical standards and specifications provide standards for interface management.…”
Section: (4) Standardizationmentioning
confidence: 99%
“…Although Wuni et al's review focuses on identifying the critical risks, there are studies that develop and apply BIM and BIM-related digital technologies for managing specific risks [10][11][12][13][14]. Most existing reviews [15][16][17][18][19] partially summarize the application areas, benefits, risks, and challenges of applying these technologies in MiC. Zou et al [20] indicated that though several reviews of traditional risk management techniques exit, there was no extensive review of BIM-based risk management research within the AEC industry.…”
Section: Knowledge Gap and Contributionmentioning
confidence: 99%